Effect of Tripolyphosphate and Ethylene Glycol Diglicidyl Ether on Chitosan Beads for Cr (VI) Adsorption - Merpiseldin Nitsae; Armeida D. R. Madjid; Lukman Hakim; Akhmad Sabarudin (Natural B, Journal of Health and Environmental Sciences, 2016)
The research about effect of tripolyphosphate (TPP) and ethylene glycol diglycidyl ether (EGDE) in preparation chitosan beads for Cr(VI) adsorption has been studied. The aim of this research was produced chitosan beads that have the ability to adsorb Cr(VI). Therefore, effect of TPP and EGDE has been studied in the research. Concentrations of TPP has varied 1%, 5%, 10%, and 15% while concentration of EGDE are 1%; 2.5%; 5%; and 7.5%. For the process adsorption chitosan beads with Cr(VI) ions used analysis with Batch method. The result shows optimum condition of chitosan beads was prepared by 5% chitosan: 5% TPP: 5% EGDE at 3 hours immersion. The adsorption capacity was 8.892 mg g-1. Which beads size was different i.e. 509-686 µm.